2011
DOI: 10.1142/s1793048011001257
|View full text |Cite
|
Sign up to set email alerts
|

ON ELECTRICAL CORRELATES OF PHYSARUM POLYCEPHALUM SPATIAL ACTIVITY: CAN WE SEE PHYSARUM MACHINE IN THE DARK?

Abstract: Plasmodium of Physarum polycephalum is a single cell visible by unaided eye, which spans sources of nutrients with its protoplasmic network. In a very simple experimental setup we recorded electric potential of the propagating plasmodium. We discovered a complex interplay of short range oscillatory behavior combined with long range, low frequency oscillations which serve to communicate information between different parts of the plasmodium. The plasmodium's response to changing environmental conditions forms ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…The model uses the multi-agent approach introduced by Jones whereby simple, low-level interactions within a multi-agent collective generate emergent transport networks, which exhibit the network minimisation behaviors seen in Physarum [26] . We use a modification of the model introduced by Adamatzky and Jones in order to cater for foraging, growth and adaptation behavior of the plasmodium, and its reaction to attracting and repelling sources [15] . Fig.…”
Section: Discussion: Modelling and Real-time Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The model uses the multi-agent approach introduced by Jones whereby simple, low-level interactions within a multi-agent collective generate emergent transport networks, which exhibit the network minimisation behaviors seen in Physarum [26] . We use a modification of the model introduced by Adamatzky and Jones in order to cater for foraging, growth and adaptation behavior of the plasmodium, and its reaction to attracting and repelling sources [15] . Fig.…”
Section: Discussion: Modelling and Real-time Synthesismentioning
confidence: 99%
“…Physarum polycephalum produces electrical activity: the movement of intra-cellular components inside the plasmodium's body and its protoplasmic tubes, and migration of the plasmodium over a substrate, produce electricity that can be measured with electrodes [13,14] . Recently Adamatzky and Jones [15] studied the electrical activity of such plasmodium and they found patterns of electrical activity, which uniquely characterise the plasmodium's spatial dynamics and physiological state. Different measurements of electrical potentials, or voltages, indicated when the plasmodium occupied and when it left specific sites of its substrate.…”
Section: Introductionmentioning
confidence: 99%
“…If recorded in isolated zones of colonisation over the duration of it being active, patterns emerge that correlate to spatial activity and environmental conditions. Adamatzky and Jones have examined such patterns and have reported that they can be used to denote the plasmodium's behaviour and physiological state [6].…”
Section: Project Backgroundmentioning
confidence: 99%
“…Indeed, in Ref. [17], Adamatzky and Jones suggest that certain patterns in plasmodial activity may serve to communicate instructions between different parts of the organism. For a more comprehensive review of the electrical properties of the P. polycephalum plasmodium, please see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The P. polycephalum plasmodium has been demonstrated to respond to stimuli such as application of physical pressure [7], chemical gradients [5] and alterations in environmental temperature [18] in a characteristic fashion. Furthermore, morphological transformations into different life cycle forms also tend to be accompanied by an archetypal pattern of electrical activity [17]. The mechanisms underlying these responses are complex, but are essentially reflections of how the plasmodium responds to the stimulus.…”
Section: Introductionmentioning
confidence: 99%